PENGARUH APLIKASI PUPUK ORGANIK CAIR (POC) KOTORAN KAMBING DAN SAPI TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Usodri, Kresna Shifa; Utoyo, Bambang; Riniarti, Dewi; Widiyani, Dimas Prakoswo; Sari, Resti Puspa Kartika; Guna, M. Mulya Adi (Universitas Lampung, 2025)
This study investigates the efficacy of liquid organic fertilizers (POC) derived from goat and cow manure as environmentally friendly alternatives for enhancing oil palm seedling growth. Conducted at the Oil Palm Nursery Unit of Politeknik Negeri Lampung (January–June 2024), the experiment employed a factorial randomized block design. Two factors were tested: POC from goat manure (0, 100, and 200 ml per seedling) and POC from cow manure (same levels). Growth parameters observed included seedling height, stem diameter, leaf count, leaf chlorophyll content, and leaflet area. Data were analyzed using ANOVA at a 5% significance level, followed by Least Significant Difference tests for mean comparison where applicable. Results show that goat manure POC at 200 ml per seedling significantly improved seedling height, leaf count, and chlorophyll content, while cow manure POC at the same dose enhanced height, stem diameter, and leaf number most effectively. No significant interaction effect between goat and cow manure treatments on any growth parameter was observed. These findings suggest that both goat and cow manure-derived liquid organic fertilizers, applied at 200 ml per seedling biweekly, can optimally support early growth of oil palm seedlings. However, their combined application did not yield synergistic benefits. The use of these organic fertilizers offers a sustainable alternative to conventional synthetic fertilizers and may contribute to improved nursery management practices in oil palm cultivation.